Perceived successfulness of e-learning curriculum development / Yap May Lin, Noor Habibah Arshad, Mohd. Aliff Sarjani - Yap, May Lin; Arshad, Noor Habibah; Sarjani, Mohd. Aliff (Penerbit UiTM (UiTM Press), 2008)
E-learning may become one of the most prominent technology enabler of providing education to the masses. However, if its curriculum is inadequately planned and poorly managed, Institutions of Higher Learning (IHLs) may require some re-engineering to make it right and in doing so, tie up management resources. This study seeks to determine the perceived successfulness of e-learning curriculum development in the Malaysian environment from the perspectives of the learner, instructor and institution, respectively. Six factors (needs analysis, collaborative development, consistency and standardization, attention to the delivery mode, expertise, and training support) associated with curriculum development are used for this determination. The primary data for this study was collected by means of a questionnaire survey conducted among 14 Malaysian private and public IHLs. Returned questionnaires totaled 140 from institutions, 145 from instructors and 180 from learners. Findings from the survey indicate that, from the perspectives of the learner, instructor and institution, all six factors exhibit significant association with the level of perceived successfulness in e-learning curriculum development. Through the findings, IHLs would be better able to focus on strengthening some crucial aspects of curriculum development that would contribute to a better planned e-learning curriculum.